TRANSLATING THE DRAMATIC TEXT - Mota, Eduarda Maria Ferreira da (2019)
This article studies the translation of dramatic texts and its particularities. It focuses the double status of drama as verbal text (for the reader) and audiovisual experience (for the spectator) and considers the translating strategies that are reader-oriented and those which are performance-oriented. Finally, it presents the concept of dramatic potential, proposing a subdivision of the concept and its application to the reflection and analysis of the translation of dramatic texts.